An Unusual Cause of Carbon Monoxide Poisoning: Narghile Smoking - Ateş, Alpay (Am J Case Rep, 2016)
Patient: Male, 27 Final Diagnosis: Carbon monoxide poisoning Symptoms: Dizziness • nausea • Syncope Medication: — Clinical Procedure: O2 treatment Specialty: Anesthesiology OBJECTIVE: Challenging differential diagnosis BACKGROUND: Carbon monoxide (CO) poisoning is commonly seen during the winter season in Turkey due to use of charcoal stoves and water heaters, but narghile smoking is a rare cause of CO poisoning. CASE REPORT: In this paper, we report a CO poisoning case caused by narghile smoking. The patient was admitted to the ED with nausea, dizziness, vertigo, and syncope. CONCLUSIONS: The diagnosis of CO poisoning depends on suspicious anamnesis. The major treatment of CO poisoning is oxygen supply.